'Ordinary, the Same as Anywhere Else': Notes on the Management of Spoiled Identity in 'Marginal' Middle-Class Neighbourhoods - Allen, Chris and Powell, Ryan and Casey, Rionach and Coward, Sarah (Sociology, 2007)
Urban sociologists are bec oming increasingly interested in neighbourhood as a source of middle-class identity. Particular emphasis is currently being given to two types of middle-class neighbourhood; gentrified urban neighbourhoods of 'distinction' and inconspicuous 'suburban landscapes of privilege'. However, there has been a dearth of work on 'marginal' middle-class neighbourhoods that are similarly 'inconspicuous' rather than distinctive, but less exclusive, thus containing sources of 'spoiled identity'. This article draws on data gathered from two 'marginal' middleclass neighbourhoods that contained a particular source of 'spoiled identity': social renters. Urban sociological analyses of neighbour responses to these situations highlight a process of dis-identification with the maligned object, which exacerbates neighbour differences. Our analysis of data from the 'marginal' middle-class neighbourhoods suggests something entirely different and Goffmanesque. This entailed the management of spoiled identity, which emphasized similarities rather than differences between neighbours.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80Mjg1Njk4NA